Combinatorial CRISPR Interference Library for Enhancing 2,3-BDO Production and Elucidating Key Genes in Cyanobacteria - Li, Hung; Pham, Nam Ngoc; Shen, Claire R.; Chang, Chin-Wei; Tu, Yi; Chang, Yi-Hao; Tu, Jui; Nguyen, Mai Thanh Thi; Hu, Yu-Chen (Frontiers in Bioengineering and Biotechnology, 2022)
Cyanobacteria can convert CO2 to chemicals such as 2,3-butanediol (2,3-BDO), rendering them promising for renewable production and carbon neutralization, but their applications are limited by low titers. To enhance cyanobacterial 2,3-BDO production, we developed a combinatorial CRISPR interference (CRISPRi) library strategy. We integrated the 2,3-BDO pathway genes and a CRISPRi library into cyanobacterium PCC7942 using the orthogonal CRISPR system, to overexpress pathway genes and attenuate genes that inhibit 2,3-BDO formation. The combinatorial CRISPRi library strategy allowed us to inhibit fbp, pdh, ppc and sps (which catalyzes synthesis of fructose-6-phosphate, acetyl-coenzyme A, oxaloacetate and sucrose, respectively) at different levels, thereby allowing for rapid screening of a strain that enhances 2,3-BDO production by almost 2-fold to 1583.8 mg/l. Coupled with a statistical model, we elucidated that differentially inhibiting all 4 genes enhances 2,3-BDO synthesis to varying degrees. fbp and pdh suppression exerted more profound effects on 2,3-BDO production than ppc and sps suppression, and these 4 genes can be repressed simultaneously without mutual interference. The CRISPRi library approach paves a new avenue to combinatorial metabolic engineering of cyanobacteria.